The Deconstruction of the Common Link Theory: Harald Motzki’s Methodological Critique of G.H.A. Juynboll’s Skepticism in Hadith Dating: Kritik Harald Motzki Terhadap Teori Common Link Juynboll - Ihsan J Junus; Dede Muhamad wahyudin; Mohammad Najib; Ali Masrur; Saifudin Nur (Diroyah : Jurnal Studi Ilmu Hadis, 2025)
The dating of hadith remains a contested frontier in the academic study of early Islam. G.H.A. Juynboll, refining Joseph Schacht’s legacy, advanced the common link theory, which treats the convergence point of transmission chains as the historical originator and probable fabricator of a tradition, while dismissing single strands as fictitious. This article reconstructs Harald Motzki’s methodological critique of that theory as articulated in Whither Hadith-Studies? and Dating Muslim Traditions, and subjects both positions to a dialectical reading. Using a qualitative library-research design with content, comparative, and interpretive analysis of primary sources, the study maps the scholarly factions involved and isolates the first principles on which each argument rests. The findings show that Juynboll’s identification of the common link with a forger relies on an argumentum e silentio and on a statistically unrealistic model of branching transmission, whereas Motzki reframes the common link as the first systematic collector and professional teacher, and grounds dating in the correlation of isnad and  matn. The article further argues that the isnad-cum- matn method does not escape critique, since it confronts a structural circularity that recent scholarship has termed a principle of uncertainty. The contribution lies in offering Indonesian hadith studies a non-apologetic synthesis that neither absolutizes skepticism nor treats Motzki’s rebuttal as a closed verdict